Violência de gênero e a atuação da delegacia da mulher na Amazônia paraense - NEVES, Luciana Carvalho das (2021)
This research is about gender violence in the municipality of Bragança, Amazonia Paraense and the practices of the Specialized Police Department for Women (DEAM) Bragança / PRO PAZ Integrated - 6th Integrated Region of Public Security (RISP) Caeté. Thus, the general objective is to analyze the practice of state agents through complaints of gender violence in 2017. We note that since its implementation, the Braganza DEAM has been working to combat gender violence in the municipality of Bragança- PA; that the majority care of the professionals of the institution researched is aimed at women who are in social vulnerability and it is emphasized that the implantation of this institution in the municipality researched is a milestone for the issue of combating domestic violence against women, children, adolescents, elderly.